2014
DOI: 10.1177/147470491401200307
|View full text |Cite
|
Sign up to set email alerts
|

Parental Mate Choice Manipulation Tactics: Exploring Prevalence, Sex and Personality Effects

Abstract: Parents and children are genetically related but not genetically identical, which means that their genetic interests overlap but also diverge. In the area of mating, this translates into children making mate choices that are not in the best interest of their parents. Parents may then resort to manipulation in order to influence their children's mating decisions in a way that best promotes the former's interests. This paper attempts to identify the structure of manipulation tactics that parents employ on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…For instance, they may be carried away in relationships with individuals who physically abuse them or who do not intend to establish a committed relationship. As this decreases, in the fitness of children and their parents, the latter have the incentive to intervene in order to correct the situation (Apostolou and Papageorgi 2014). And parents can be effective in doing so because they are older and more experienced, and their judgment is not clouded by high levels of libido or love; so in many instances, they may be better able to identify cost-inflicting mates than their children.…”
Section: Agreement and Disagreement Over Mate Choicementioning
confidence: 99%
See 4 more Smart Citations
“…For instance, they may be carried away in relationships with individuals who physically abuse them or who do not intend to establish a committed relationship. As this decreases, in the fitness of children and their parents, the latter have the incentive to intervene in order to correct the situation (Apostolou and Papageorgi 2014). And parents can be effective in doing so because they are older and more experienced, and their judgment is not clouded by high levels of libido or love; so in many instances, they may be better able to identify cost-inflicting mates than their children.…”
Section: Agreement and Disagreement Over Mate Choicementioning
confidence: 99%
“…Research has identified several traits, including beauty (a proxy of genetic quality), good family background, exciting personality, and similar religious background, which are preferred differently by parents and their children (Apostolou 2014;Buunk et al 2008;Dubbs and Buunk 2010;Perilloux et al 2011). This indicates that when they choose a mate, children are likely to find spouses who do not comply with the preferences of their parents.…”
Section: Agreement and Disagreement Over Mate Choicementioning
confidence: 99%
See 3 more Smart Citations